Change of anti-Mullerian-hormone levels during follicular phase in PCOS patients. (15th September 2014) - Köninger, A.; Koch, L.; Enekwe, A.; Birdir, C.; Kasimir-Bauer, S.; Kimmig, R.; Strowitzki, T.; Schmidt, B.
Abstract: Anti-Mullerian-hormone (AMH) does not seem to fluctuate significantly during the menstrual cycle in healthy women. However, little is known about cycle fluctuations of AMH levels in patients with polycystic ovarian syndrome (PCOS). The purpose of this study was to examine AMH fluctuations during the follicular phase in PCOS patients receiving antiestrogens or recombinant follicle-stimulating hormone (FSH). About 40 PCOS patients diagnosed according to Rotterdam ESHRE/ASRM-Sponsored PCOS Consensus Workshop Group 2003 and 19 controls were prospectively enrolled. PCOS patients received either antiestrogens or recombinant FSH for monoovulation induction and controls received antiestrogens. AMH levels were determined (1) between the 2nd and the 5th day of follicular phase and (2) when a single large dominant follicle ≥18 mm had appeared. Our study shows that AMH levels do not change during follicular development in controls as well as in PCOS patients with AMH levels   < 5 ng/ml, irrespective of antiestrogen or FSH therapy. However, in PCOS patients with AMH levels ≥5 ng/ml, AMH declines significantly during follicular development ( p  < 0.01). We conclude that AMH levels should be determined in the early follicular phase in PCOS patients without the influence of antiestrogens or exogenous FSH, because these interventions may lower AMH values in patients with high levels. Chinese abstract: 抗苗勒管激素（AMH）在健康妇女月经周期中似乎并没有明显波动。然而多囊卵巢综合征（PCOS）患者月经期AMH水平的变化却鲜为人知。本研究的目的是检测PCOS患者卵泡期接受抗雌激素或重组卵泡刺激素（FSH）治疗后AMH水平的波动。其中40名患者诊断为PCOS（根据2003年欧洲人类生殖与胚胎学会和美国生殖医学会发起的PCOS共识研讨会），19人纳入对照组。PCOS患者采用抗雌激素或重组FSH诱发单卵泡发育，对照组接受抗雌激素治疗。(1)月经第2天至第5天和（2）出现单个优势卵泡（卵泡直径≥18mm）时分别监测AMH水平。我们的研究表明无论是否接受抗雌激素或FSH治疗，对照组和AMH＜5ng/ml的PCOS组AMH水平在卵泡发育过程中并没有波动。而AMH＞5ng/ml的PCOS组，AMH在卵泡发育过程中则显著下降（ P ＜0.01）。我们得出结论PCOS患者AMH水平应在没有接受抗雌激素或外源FSH治疗的早卵泡期测定，因为对于高AMH水平的PCOS患者这些干预治疗可能会降低AMH水平。